Light‐Induced Electron Transfer Toward On/Off Room Temperature Phosphorescence in Two Photochromic Coordination Polymers - Feng, Dong‐Xue; Mu, Ying; Li, Jie; De Han, Song‐; Li, Jin‐Hua; Sun, Hui‐Li; Pan, Mei; Hu, Ji‐Xiang; Wang, Guo‐Ming (Advanced functional materials, 2023)
Photoswitchable room temperature phosphorescence (RTP) materials are of great interest due to their potential applications in optical devices and switches. Herein, two Zn‐based coordination polymers (CPs) (H3‐TPB)·[Zn6(H‐HEDP)(HEDP)3(H2O)2]·5H2O (complex 1; HEDP = hydroxyethylidene diphosphonate; TPB = 1,3,5‐tris(4‐pyridyl)benzene) and (H‐TPB)·[Zn3(H‐HEDP)(HEDP)(H2O)]·2H2O (complex 2) with distinguishable photochromism and tunable RTP are synthesized involving photoactive TPB molecules with different packing modes. Complex 1 exhibits bidirectionally on/off RTP regulation via on‐switch with excitation of 250−330 nm light and off‐switch with 350−380 nm, and the “turn‐on” behavior can be attributed to the advance of Förster resonance energy transfer‐assisted intersystem crossing (ISC) process while “turn‐off” process due to the transformation from H3‐TPB cations to H3‐TPB· radicals. Complex 2 exhibits photoswitchable RTP accompanied with reversible photochromism by leveraging the self‐absorption and RTP emission. Two demos based on the above compounds are further applied to demonstrate the application in information recording and encryption fields. This work supplies a strategy toward the design of switchable RTP systems using electron transfer photochromism, shedding light on broadening the frontiers of photoresponsive materials. This study for the first time exhibits the bidirectional on/off room temperature phosphorescence regulation via on‐switch with excitation of 250−330 nm and off‐switch with 350−380 nm light irradiation in an electron transfer photochromic complex, and two demos are further applied to demonstrate the application of the compounds in information recording and encryption fields.